Her mouth as souvenir - Gibbons, Heather June (Agha Shahid Ali prize in poetry., 2018)
"In a startling voice propelled by desire and desperation on the verge of laughter, these poems leap from the mundane to the sublime, from begging to bravado, from despair to reverie, revealing the power that comes from hanging on by a thread. Poet Heather June Gibbons conjures belief in the absence of faith, loneliness in the digital age, beauty in the face of absurdity; all through the cataract of her sunglasses' cracked lens. In this debut collection, we are shown a world so turbulent, anxious, and beautiful, we know it must be ours. Under pressure, these poems sing"--Provided by publisher